Extreme deformability of insect cell membranes is governed by phospholipid scrambling - Shiomi, Akifumi; Nagao, Kohjiro; Yokota, Nobuhiro; Tsuchiya, Masaki; Kato, Utako; Juni, Naoto; Hara, Yuji; Mori, Masayuki X.; Mori, Yasuo; Ui-Tei, Kumiko; Murate, Motohide; Kobayashi, Toshihide; et al. (Cell reports, 2021)
Organization of dynamic cellular structure is crucial for a variety of cellular functions. In this study, we report that Drosophila and Aedes have highly elastic cell membranes with extremely low membrane tension and high resistance to mechanical stress. In contrast to other eukaryotic cells, phospholipids are symmetrically distributed between the bilayer leaflets of the insect plasma membrane, where phospholipid scramblase (XKR) that disrupts the lipid asymmetry is constitutively active. We also demonstrate that XKR-facilitated phospholipid scrambling promotes the deformability of cell membranes by regulating both actin cortex dynamics and mechanical properties of the phospholipid bilayer. Moreover, XKR-mediated construction of elastic cell membranes is essential for hemocyte circulation in the Drosophila cardiovascular system. Deformation of mammalian cells is also enhanced by the expression of Aedes XKR, and thus phospholipid scrambling may contribute to formation of highly deformable cell membranes in a variety of living eukaryotic cells.
Gesehen am 27.07.2021